Developing The Coffee Production In Ciamis, Indonesia - Mauladi, Mochamad Arief Rizki; Mulyo, Jangkung Handoyo; Darwanto, Dwidjono Hadi (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
Ciamis Regency is a coffee-producing area in West Java. Most of the coffee beans in Ciamis Regency are distributed outside the regency and are not utilized by local Coffee SMEs which are already widely spread in Ciamis Regency. This is because the quality of the coffee produced has not been able to meet the expectations of the coffee market. In addition, there is no appropriate coffee development strategy according to the conditions faced in Ciamis Regency. This study aims to formulate the appropriate development strategy according to the conditions faced. This study used a sample of key informants consisting of 30 coffee farmers, the head of the agriculture department and the head of the plantation and horticulture sector, the owner of The History Coffee coffee shop and the owner of The Ki Oyo coffee processing company. SWOT analysis is used to formulate a coffee development strategy using valid and reliable internal and external factors, while the QSPM matrix is used to rank the strategic priorities. The results show that the prioritized sequence of strategies is in the form of strategies that optimize the upstream sector first (production sector) before optimizing the downstream sector (supporting and market sector).